2022
DOI: 10.1021/acs.estlett.2c00757
|View full text |Cite
|
Sign up to set email alerts
|

Deglycosylation of Two Typical Plant-Generated Glycoconjugates of Tetrabromobisphenol A through In Vitro Digestion Processes

Abstract: Tetrabromobisphenol A (TBBPA) is extensively detected in various environmental media. Its typical glycosylation products in plants, TBBPA mono-β-D-glucopyranoside (TBBPA MG) and TBBPA di-β-D-glucopyranoside (TBBPA DG), are likely to enter the human body through the oral route. The deglycosylation processes of TBBPA MG and TBBPA DG in both simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) were studied. Results showed that 68% of TBBPA MG was transformed to TBBPA after 6 h incubation in gastroin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…One possible explanation for these structures was the action of pancreatin from the pancreas, which could catalyze deglycosylation and demethylation processes. 43,44 In our investigation, we observed significant levels of metabolized STG during small intestinal digestion, aligning with earlier studies that indicate the presence of STG in the digestive pathway and its efficient metabolism by microorganisms in the excretory tract. 35,36,42,45 In summary, this study presents the first comprehensive investigation of α-glucosidase inhibitors isolated from black sesame meal using bioassay-guided isolation.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One possible explanation for these structures was the action of pancreatin from the pancreas, which could catalyze deglycosylation and demethylation processes. 43,44 In our investigation, we observed significant levels of metabolized STG during small intestinal digestion, aligning with earlier studies that indicate the presence of STG in the digestive pathway and its efficient metabolism by microorganisms in the excretory tract. 35,36,42,45 In summary, this study presents the first comprehensive investigation of α-glucosidase inhibitors isolated from black sesame meal using bioassay-guided isolation.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…The detection of the [M + H] + ion at 685.43671 indicated the removal of one glucose and two methylene groups, resulting in the proposed structures of SIF-1 (Figure ). One possible explanation for these structures was the action of pancreatin from the pancreas, which could catalyze deglycosylation and demethylation processes. , In our investigation, we observed significant levels of metabolized STG during small intestinal digestion, aligning with earlier studies that indicate the presence of STG in the digestive pathway and its efficient metabolism by microorganisms in the excretory tract. ,,, …”
Section: Results and Discussionsupporting
confidence: 90%
“…Conjugation reactions are usually reversible, and deconjugation has been proved in human digestive systems. 52,53 Specifically, phase-II conjugation product M-392 might be deconjugated to phenamacril in human gut after intake. Furthermore, metabolite like M-157 was estimated to be more toxic and persistence than phenamacril.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This study demonstrated that phloem translocation and plant excretion were important pathways to transport phenamacril from shoots to roots and rhizosphere environments, resulting in a prolonged cycling contamination, which should be considered in developing more accurate prediction models for assessing the risks of phloem-transported chemicals to ecosystems. After being taken up, phenamacril was extensively transformed (e.g., 76.4%) in plants, with nine metabolites newly identified. Conjugation reactions are usually reversible, and deconjugation has been proved in human digestive systems. , Specifically, phase-II conjugation product M-392 might be deconjugated to phenamacril in human gut after intake. Furthermore, metabolite like M-157 was estimated to be more toxic and persistence than phenamacril.…”
Section: Resultsmentioning
confidence: 99%
“…14 Our previous studies found that BPA with different halogenation patterns distinctly affects the activities toward the peroxisome proliferator-activated receptor and estrogen receptor (ER). 15 Brominated bisphenols including tetrabromobisphenol A (TBBPA) and TBBPS, the mostly used bisphenols as flame retardants in plastics, textiles, and electronic equipment, 16 T h i s c o n t e n t i s showed stronger thyroid disruption than BPA and BPS. Structural moiety differences of bisphenols are suspected to affect a variety of physiological signaling, responsible for subsequent biological defects.…”
Section: Introductionmentioning
confidence: 99%